The last kids on Earth. Quint and Dirk's hero quest - Brallier, Max (Brallier, Max. Last kids on Earth., 2022)
While Thrull and his cronies attack the Millennium Super Mall, Quint and Dirk speed to the parking garage to stop the Bone Howler who wants to attack the monsters who are fleeing to safety. Quint hopes his conjurer's cane will be enough to stop the onslaught, but when he uses it, it transports them back in time and they must find their way back if they are to help save their friends.